2021
DOI: 10.3389/fnut.2021.743324
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Status Response to Oral Nutritional Supplementation in Hemodialysis Patients With Protein Energy Wasting: A Multi-Center Randomized, Open Label-Controlled Trial

Abstract: Background: Muscle wasting, observed in patients with end-stage kidney disease and protein energy wasting (PEW), is associated with increased mortality for those on hemodialysis (HD). Oral nutritional supplementation (ONS) and nutrition counseling (NC) are treatment options for PEW but research targeting muscle status, as an outcome metric, is limited.Aim: We compared the effects of combined treatment (ONS + NC) vs. NC alone on muscle status and nutritional parameters in HD patients with PEW.Methods: This mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…For example, Bernardes et al performed a systematic review and meta‐analysis on the effect of increased energy and/or protein intake on nutritional status in obstructive pulmonary disease patients and found an increase of 0.29 cm in MAMC 34 . In HD patients, Sahathevan et al performed a 6‐month open‐label randomized controlled trial with oral nutritional supplements and found an increase in MAMC in the intervention group of 0.4 cm 35 . A precise assessment of risk reduction associated with correction of metabolic acidosis in this specific patient population is impossible, but observational data from related patient populations may provide an indication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bernardes et al performed a systematic review and meta‐analysis on the effect of increased energy and/or protein intake on nutritional status in obstructive pulmonary disease patients and found an increase of 0.29 cm in MAMC 34 . In HD patients, Sahathevan et al performed a 6‐month open‐label randomized controlled trial with oral nutritional supplements and found an increase in MAMC in the intervention group of 0.4 cm 35 . A precise assessment of risk reduction associated with correction of metabolic acidosis in this specific patient population is impossible, but observational data from related patient populations may provide an indication.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Therefore, optimizing the nutritional status through dietary interventions and possibly protein supplementation can promote muscle mass preservation and overall physical function. 39 Proper dialysis treatment is essential to manage fluid and electrolyte imbalances, which can impact muscle function. Ensuring adequate dialysis therapy is necessary for maintaining patients' overall health and muscle status.…”
Section: Discussionmentioning
confidence: 99%
“…A standard oral nutritional supplement provides up to 5 kcal/kg/day and 0.3-0.4 g/kg/day of protein [48]. In a recent randomized controlled trial, Sahathevan et al [49] found that combination of oral nutritional support with nutritional counseling was effective in treating PEW and had positive effects on muscle status in hemodialysis patients.…”
Section: Impact Of Other Nutritional Interventions On Muscle Wasting ...mentioning
confidence: 99%